Experiences of Enslaved Children in Luanda, 1850–1869 - Vanessa S. Oliveira (Genealogy)
About half of Luanda’s population comprised enslaved people in the mid-nineteenth century. Although scholars have examined the expansion of slavery in Angola after the end of the transatlantic slave trade and the use of slavery to underpin the trade in tropical commodities, the labor performed by enslaved children has been neglected. This study explores the experiences of enslaved children working in Luanda during the era of the so-called “legitimate” commerce in tropical commodities, particularly between 1850 and 1869. It draws upon slave registers, official reports, and the local gazette, the Boletim Oficial de Angola, to analyze the means through which children were enslaved, the tasks they performed, their background, family connections, and daily experiences under enslavement. This paper argues that masters expected enslaved children to perform the same work attributed to enslaved men and women. After all, they saw captives as a productive unit irrespective of their age.